Determination of Dopamine in the Presence of Ascorbic Acid Using Silver-Diethyldithiocarbamate Modified Electrode - Liu, Yue-Ying; Zhao, Shi-Hao (Asian Journal of Chemistry, 2014)
A glassy carbon electrode (GCE) was modified with silver-diethyldithiocarbamate (DDTC Ag) modified electrode has been constructed. The DDTC Ag modified electrode showed an excellent electrocatalytical effect on the oxidation of dopamine. In the pH 2.56 buffer solution, the oxidation peak of dopamine was linear with its concentration from 5.0 × 10-7 – 6.0 × 10-5 mol L-1, detect limit of it reached 1.0 × 10-7 mol L-1. Moreover, the interference of ascorbic acid with the determination of dopamine could be eliminated. The method could obtain better result when it applied to the determination dopamine in serum and medical samples.